Socio-Professional Expectations on Master Students of the Bucharest University of Economic Studies - Lelia Voinea; Camelia Stăiculescu; Ion Schileru (Amfiteatru Economic Journal, 2016)
The interest of young people for their future socio-professional was always and everywhere a dominant factor and also a notorious motivator factor in their efforts. Studies conducted by entities concerned as well as researchers from various social areas have shown that this interest is also complex and profound for current young generation. This paper is a qualitative research conducted in a prestigious faculty of the Academy of Economic Studies in Bucharest, on a number of graduate students who are preparing their studies in Business Administration; as an investigation method the free essay was used. The information from students' essays was supplemented by observations made by the teachers group - authors of the work. Research results revealed both confirmation of hypotheses and also surprises.
Keywords: A13; A14; A23; D01; Z13; 330; social-economic horizon; society's expectances; entrepreneurship; business; curriculum